Characteristics of Patients with Estrogen Receptor (ER)-Negative, Progesterone Receptor (PR)-Negative, and HER2-Negative Invasive Breast Cancer in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia from 2010 to 2011 - Nadytia Kusumadjayanti; Dharmayanti Francisca Badudu; Bethy S. Hernowo (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Breast cancer is the most common type of cancer that has been diagnosed among Indonesian women. One of the subtypes that frequently being studied is the triple negative breast cancer which has poorer prognosis among all subtypes. The objective of this study was to investigate the incidents and the characteristics of triple negative breast cancer patients.Methods: This study used triple negative breast cancer patients’ medical records in Dr. Hasan Sadikin General Hospital. Some characteristics were identified, such as age at presentation, menopause status, tumor size, stage at presentation, grades of tumor, pathological features, and metastatic status. Data were taken during 2010 and 2011 and presented in table.Results: Thirty women among 252 patients were identified as having triple negative breast cancer. Based on those 30 cases, 11 patients were in the age group of 40‒55 years. Fifteen out of 30 cases were premenopausal. From 30 cases, 14 patients had tumor size bigger than 5 cm. Sixteen cases had stage III tumor. Most of the cases were invasive ductal carcinoma mammae as their histological features. Two cases had metastized to pleura.Conclusions: The incidence rate of triple negative breast cancer in Dr. Hasan Sadikin General Hospital is 11.9% with these common characteristics: range of age are between 40 to 45 years, have a premenopausal, had >5cm tumor , stage III tumor and has histological feature IDC, and only 2 patients were metastized to pleura. DOI: 10.15850/amj.v2n3.494